Posisi Ideal Wanita Karir dalam Rumah Tangga Perspektif Al-Qur’an - Afwan, Muhammad Muhsin (UIR Press, 2025)
Nowadays, women do not only play the role of housewives. Instead, she plays an active role in meeting the family's financial needs by pursuing his profession. So that activities outside the home have a significant role in supporting family finances. However, in the household, career women are still required to provide services like women who do not work. In fact, in some cases, career women are often blamed for problems that arise in the family. The time taken to develop one's career and potential is seen as a source of conflict that shakes the family bond. This article aims to examine the ideal position of career women in the Koran, in order to educate husbands in treating working wives. The method used in this research is tafsir tahlili which examines a verse comprehensively, by placing QS Al Baqarah: 228 as the main verse with several supporting verses. The results of this research indicate that career women should be given more recognition according to the burden they bear. A husband is expected to provide assistance to his wife in doing housework, as appreciation for his wife who has helped earn a living.